2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6637836
|View full text |Cite
|
Sign up to set email alerts
|

Non-negative matrix factorization for single-channel EEG artifact rejection

Abstract: New applications of Electroencephalographic recording (EEG) pose new challenges in terms of artifact removal. In our work we target applications where the EEG is to be captured by a single electrode and a number of additional lightweight sensors are allowed. Thus, this paper introduces a new method for artifact removal for single-channel EEG recordings using nonnegative matrix factorisation (NMF) in a Gaussian source separation framework. We focus the study on ocular artifacts and show that by properly exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Damon et al proposed an eye-blink artifact reduction method based on nonnegative matrix factorization (NMF) for a single-channel EEG device [9]. They reported that NMF can effectively decompose recorded EEG signals into brain activity components and eye-blink artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Damon et al proposed an eye-blink artifact reduction method based on nonnegative matrix factorization (NMF) for a single-channel EEG device [9]. They reported that NMF can effectively decompose recorded EEG signals into brain activity components and eye-blink artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the automatic transcription [13], the sound emphasis or separation [14], and the band spreading [15]. Recently, a research of artifactitious rejection using single-channel EEG recordings is also reported [7]. However, this research has the following problem.…”
Section: B Preparing Datasets For Proposed Methodsmentioning
confidence: 98%
“…A blink artifact removal method using single-channel EEG recordings and non-negative matrix factorization (NMF) had been reported [7]. The NMF was showed the effectivity for blink artifact rejection.…”
Section: Introductionmentioning
confidence: 98%
“…Some works reported that the supervised NMF could effectively factorize the observed EEG signals into the brain activity components and the artifacts if the user has artifact data in advance [62,63]. Before applying supervised learning, template matrix X Art has been factorized into H Art and W Art .ThematrixX is continuously factorized into H and W where H contains the elements of matrix H Art .…”
Section: Nonnegative Matrix Factorizationmentioning
confidence: 99%